Arabic Historical Literature from Ghadāmis and Mali : a Documents from the 18th to 20th Century - Norris, Harry T., (Islam in Africa ;, 2020)
In this work translations of four texts are provided from Ghadāmis and from Mali. The first is a biography of the Ghadāmisī scholar ʿAbdallāh b. Abī Bakr al-Ghadāmisī (1626-1719 AD), written by the eighteenth-century author Ibn Muhalhil al-Ghadāmisī. A second text is "The History of al-Sūq", concerning al-Sūq, the historic town of Tādmakka and the original home of the Kel-Essouk Tuareg. The third text is "The Precious Jewel in the Saharan histories of the 'People of the Veil'" by Muḥammad Tawjaw al-Sūqī al-Thānī, a contemporary Tuareg author. It pertains to the Kel-Essouk and their historical ties with the Maghreb and West Africa. The final text is a description of the Tuareg from the book "Ghadāmis, its features, its images and its sights" by Bashīr Qāsim Yūshaʿ, published in Arabic in 2001 AD.